New attack on Kotzig's conjecture - Christian Barrientos; Sarah M. Minion (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2016)
In this paper we study a technique to transform α -labeled trees into ρ -labeled forests. We use this result to prove that the complete graph K_2n+1 can be decomposed into these types of forests. In addition we show a robust family of trees that admit ρ -labelings, we use this result to describe the set of all trees for which a ρ -labeling must be found to completely solve Kotzig's conjecture about decomposing cyclically the complete graph K_2n+1 into copies of any tree of size n.